2022
DOI: 10.1101/2022.12.21.521303
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reactivation of early-life stress-sensitive neuronal ensembles contributes to lifelong stress hypersensitivity

Abstract: Early-life stress (ELS) is one of the strongest lifetime risk factors for depression, anxiety, suicide, and other psychiatric disorders, particularly after facing additional stressful events later in life. Human and animal studies demonstrate that ELS sensitizes individuals to subsequent stress. However, the neurobiological basis of such stress sensitization remains largely unexplored. We hypothesized that ELS-induced stress sensitization would be detectable at the level of neuronal ensembles, such that cells … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…Another future goal will be to merge this cell-type specificity with tracking of the same cells throughout the lifespan, which will overcome our current limitation of examining adolescent and adult outcomes in different animals. Recent work has shown that a stress exposure early, in the form of maternal separation, led to the prolonged sensitivity of a set of cells in the nucleus accumbens to stressors in adulthood (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another future goal will be to merge this cell-type specificity with tracking of the same cells throughout the lifespan, which will overcome our current limitation of examining adolescent and adult outcomes in different animals. Recent work has shown that a stress exposure early, in the form of maternal separation, led to the prolonged sensitivity of a set of cells in the nucleus accumbens to stressors in adulthood (40).…”
Section: Discussionmentioning
confidence: 99%
“…Another future goal will be to merge this cell-type specificity with tracking of the same cells throughout the lifespan, which will overcome our current limitation of examining adolescent and adult outcomes in different animals. Recent work has shown that a stress exposure early, in the form of maternal separation, led to the prolonged sensitivity of a set of cells in the nucleus accumbens to stressors in adulthood (40). Using a transgenic strategy in mice to permanently mark cells that had increased Arc expression in response to early life stress, Balouek et al showed that neurons tagged by maternal separation were the same cells reactivated by stress later in life and that blocking their activation ameliorated the negative behavioral consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Early life stress (ELS) affects healthy development and aging as well as susceptibility to psychiatric disorders in humans [1][2][3][4] . Studies in humans and animals suggest ELS may increase risk for psychiatric diseases such as depression by inducing hypersensitivity to future stress exposure [5][6][7][8] . However, mechanism by which ELS sensitizes responses to future stress responses in adulthood remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal separation, a well-established model of early-life stress, has been extensively studied to investigate the long-term consequences of adverse early life events during this critical period of brain function and behaviour (Taylor et al, 2010; Korosi et al, 2012). Stress due to maternal separation (MS) in rodents leads to anxiety-like behaviours in adulthood as characterized by heightened fear, avoidance, and stress sensitivity (Banqueri et al, 2017; Lundberg et al, 2020; Balouek et al ., 2023). The ventral hippocampus, a key brain area affected by MS (Dimatelis et al, 2014; Marais et al, 2009), has been shown to regulate emotions (Jimenez et al, 2018; H. Li et al, 2022; McNaughton, 1997).…”
Section: Introductionmentioning
confidence: 99%